2015
DOI: 10.1080/02678292.2014.960487
|View full text |Cite
|
Sign up to set email alerts
|

Liquid crystal alignment behaviours on poly(methyl methacrylate) having polyhedral oligomeric silsesquioxane groups

Abstract: 2015) Liquid crystal alignment behaviours on poly(methyl methacrylate) having polyhedral oligomeric silsesquioxane groups, Liquid Crystals, 42:1, 32-40, A series of poly(methyl methacrylate) derivatives containing polyhedral oligomeric silsesquioxane (POSS) groups (MCP#) were synthesised via free radical polymerisation (FRP) using methacryl isobutyl POSS (MA-POSS) and methyl methacrylate as monomers to investigate liquid crystal (LC) alignment property of these polymer films. The LC cells made from the films o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…3,9 1. 5,15 1 7,13 ]octasiloxan-1-yl)propyl methacrylate), 39.79, 10.63, and 22.70 mN/m, respectively, 64,65 it is assumed that the hydrophobicity of the HCPM moiety is sufficient to interrupt the formation of a continuous oil-fouling film.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…3,9 1. 5,15 1 7,13 ]octasiloxan-1-yl)propyl methacrylate), 39.79, 10.63, and 22.70 mN/m, respectively, 64,65 it is assumed that the hydrophobicity of the HCPM moiety is sufficient to interrupt the formation of a continuous oil-fouling film.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Though these attempts could create a more soluble modified PI, main-chain-type PIs are still unable to satisfy the requirements of manufacturing high-performance LCDs. Recently, it was reported that LCDs with vertical alignment mode had a faster response time and a higher contrast ratio compared to that with parallel aligned mode, [9,10] and there are several materials which could use to induce liquid crystals (LCs) to align vertically, such as poly(methyl methacrylate) with polyhedral oligomeric silsesquioxane groups, [11] PI with long side chains. [12] PIs attracted a lot of scientific interest because of their good performance.…”
Section: Introductionmentioning
confidence: 99%
“…[22,23] POSS segment has also been introduced to the liquid crystalline (LC) materials in order to improve the thermal stability and to promote the tendency to form the LC phase. [24][25][26] Generally, POSS liquid crystalline materials include three major groups, that is, both the mesogenic moieties and POSS as side chains, [27,28] POSS as a core and one or several mesogenic moieties as side chains [29][30][31][32] and starshaped POSS LC polymers. [33] The star-shaped POSS LC polymer is a kind of macromolecular LC with POSS as the branching point (core) and several polymeric LC as arms.…”
Section: Introductionmentioning
confidence: 99%